Synthesis, Characterization of Some New 2-Azetidinone Derivatives - Monther Faisal Mahdi; Rafah Fadhel Al-Smaism; Ammar Ihsan Mahmood (College of Pharmacy / Mustansiriyah University, 2015)
New series of 2-Azetidinone (4a-4f) were synthesized, the structure of these new derivativeswereconfirmed using spectral methods starting from Ketoprofen we prepared an amide ester by using DCC and TEA in DCM, then converted to hydrazide by using hydrazine hydrate, then a Schiff bases were synthesized using different aromatic aldehydes in ethanol, and the final compounds were obtained by cyclocondensation using chloroacetylechloride.  The synthesis of the designed compounds has been successfully achieved. Purity and characterization were confirmed by determination of physical properties (melting points &Rf values), FT-IR spectroscopy and 1H-NMR Sp.